Scabies- Major Childhood Skin Infestation in Bangladesh - An Updated Review (The Journal of Ad-din Women's Medical College, 2023)
Background: Globally distributed scabies- a highly prevalent contagious skin disease particularly infests children and elderly population. Since scabies often remain un-recognized/un-diagnosed or under-reported, but >130 million people suffer from scabies, WHO listed it under neglected tropical disease (NTD).Objective(s): This updated review focus on scabies etiology and association with socio-economic profile, water sanitation, personal hygiene, poor living condition, and environmental pollution. However, few plausible risk factors of childhood scabies have also been covered in this review.Methodology: A through computer-based literature search was performed for the period of ~two decades (2000 through 2022) utilizing four familiar search engines: Google Scholar, PubMed, Scopus and Elsevier. The search topics covered: „childhood/adult scabies‟, „etiology‟, „risk factors‟, „monthly income‟, „water sanitation „personal hygiene‟, „living conditions‟ and few others (optional).Findings: Of total 28 published articles reviewed conducted in major lower/mid income countries (LMICs) including some rich and Western ones. Overall findings revealed